Avaliação técnico-econômica da troca de motores em parques fabris de médio porte: simulação de cenários em regiões distintas do Brasil - Gonçalves Júnior, Adriano Araújo (Universidade Federal Rural do Semi-Árido, 2021)
In the search for more efficient energy consumption, actions aimed at replacement of induction motors for more efficient motors in industrial parks with a great diversification of motors have been consolidated as one of the main investments aimed at energy efficiency. From this perspective, this study aims to reliably determine information about the cost-effectiveness of replacement electric motors for more efficient motors in similar medium-sized industrial parks located in different regions of Brazil, and thus, determine in terms of economic profitability the best region in Brazil in the industrial consumption class to carry out the replacement of induction motors. For this purpose, electricity consumption and revenue data were collected and stratified. Based on them, the electricity escalation rate by region of Brazil were calculated. Therefore, a specific simulator was built to automate the replacement of electric motors. It takes into account life cycle cost analysis (LCC) to determine the technical-economic cost-effectiveness of the replacement. Subsequently, the simulator was applied in a case study that was carried out in order to show the validation of the values found and the effectiveness of the applied method. The study started from the assumption of a medium-sized consumer goods industry with two branches in different regions: Northeast, Southeast and Midwest of Brazil. The results proved to be satisfactory, since all the objectives proposed in the work were achieved. Data referring to technical-economic cost-effectiveness showed that the best region to carry out the replacement of electric motors for the industrial consumption class is the Midwest region of Brazil. Furthermore, variations in the loading values of the replacement options proved to be decisive in determining the viability of the replaced motors
Keywords: Economia Líquida; Rentabilidade; Motor de indução; Taxa de Escalada; Custo de Ciclo de Vida (CCV); Net Savings; Cost-Effectiveness; Induction Motor; Electricity Escalation Rate; ENGENHARIAS::ENGENHARIA ELETRICA